Osteohistology of Greererpeton provides insight into the life history of an early Carboniferous tetrapod. Issue 6 (26th July 2021) - Whitney, Megan R.; Pierce, Stephanie E.
Abstract: The vertebrate transition to land is one of the most consequential, yet poorly understood periods in tetrapod evolution. Despite the importance of the water–land transition in establishing modern ecosystems, we still know very little about the life histories of the earliest tetrapods. Bone histology provides an exceptional opportunity to study the biology of early tetrapods and has the potential to reveal new insights into their life histories. Here, we examine the femoral bone histology from an ontogenetic series of Greererpeton, an early tetrapod from the Middle‐Late Mississippian (early Carboniferous) of North America. Thin‐sections and micro‐CT data show a moderately paced rate of bone deposition with significant cortical thickening through development. An interruption to regular bone deposition, as indicated by a zone of avascular tissue and growth marks, is notable at the same late juvenile stage of development throughout our sample. This suggests that an inherent aspect to the life history of juvenile Greererpeton resulted in a temporary reduction in bone deposition. We review several possible life history correlates for this bony signature including metamorphosis, an extended juvenile phase, environmental stress, and movement (migration/dispersal) between habitats. We argue that given the anatomy of Greererpeton, it is unlikely that events related to polymorphism (metamorphosis, extended juvenile phase) can explain the bony signature observed in our sample. Furthermore, the ubiquity of this signal in our sample indicates a taxon‐level rather than a population‐level trait, which is expected for an environmental stress. We conclude that movement via dispersal represents a likely correlate, as such events are a common life history strategy of aquatically bound vertebrates. Abstract : The bone histology from an ontogenetic series of the early tetrapod, Greererpeton, reveals a peculiar life history event highlighted by the yellow band in our schematic. It is possible that the period of stress endured by juvenile Greererpeton represents a dispersal event from natal to adult waterbodies.